2013
DOI: 10.1109/tns.2013.2270089
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive & Systematic Study of Coincidence Time Resolution and Light Yield Using Scintillators of Different Size and Wrapping

Abstract: Over the last years, interest in using time-of-flightbased Positron Emission Tomography (TOF-PET) systems has significantly increased. High time resolution in such PET systems is a powerful tool to improve signal to noise ratio and therefore to allow smaller exposure rates for patients as well as faster image acquisition. Improvement in coincidence time resolution (CTR) in PET systems to the level of 200 ps FWHM requires the optimization of all parameters in the photon detection chain influencing the time reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 32 publications
4
24
0
Order By: Relevance
“…Note that the x-axis of this figure represents total detection efficiency, and it is comprised of both light collection efficiency at the exit interface of the crystal and the PDE of the photosensor used to convert scintillation light into charge. The light collection at the exit of crystal elements with polished surfaces and lengths of 20 mm is typically reported between 40–60% [Lőrincz et al 2010, Bauer et al 2009, Auffray et al 2013, Pauwels et al 2009, Levin et al 2002]. The PDE of a photosensor tends to be between 20–30% for photomultipliers with bialkili photocathodes, and analogue SiPMs typically have an effective PDE of 30–35% when operated at a sufficient margin above the breakdown voltage, which is the case when the bias is optimized for timing measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the x-axis of this figure represents total detection efficiency, and it is comprised of both light collection efficiency at the exit interface of the crystal and the PDE of the photosensor used to convert scintillation light into charge. The light collection at the exit of crystal elements with polished surfaces and lengths of 20 mm is typically reported between 40–60% [Lőrincz et al 2010, Bauer et al 2009, Auffray et al 2013, Pauwels et al 2009, Levin et al 2002]. The PDE of a photosensor tends to be between 20–30% for photomultipliers with bialkili photocathodes, and analogue SiPMs typically have an effective PDE of 30–35% when operated at a sufficient margin above the breakdown voltage, which is the case when the bias is optimized for timing measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The generally high refractive index of the scintillators and the consequently small critical angle will lower this efficiency. Several studies ( [21][22][23]) demonstrated also that the surface state, the edge quality and the type of wrapping used for the crystal play an important role in the efficiency of light collection η coll .…”
Section: Limits On Light Yieldmentioning
confidence: 99%
“…The majority of these studies have used short crystals, either 1 or 5mm in length, in order to minimise self-absorption and photon refection effects in the crystal. These effects have been shown to deteriorate the energy and time resolution in longer crystals [13], [33]. All the samples detailed in the table were grown by the Cz method except for the first one which was grown by the micropull-down method (µPD).…”
Section: Introductionmentioning
confidence: 99%